Ocean Station Vessel Observations - Cooperative Institute For Research In Environmental Sciences/University Of Colorado; National Climatic Data Center/NESDIS/NOAA/U.S. Department Of Commerce; Ocean Climate Laboratory/National Oceanographic Data Center/NESDIS/NOAA/U.S. Department Of Commerce; Research Data Archive/Computational And Information Systems Laboratory/National Center For Atmospheric Research/University Corporation For Atmospheric Research (UCAR/NCAR - Research Data Archive, 1980)
Surface observations, some XBT profiles, and some subsurface station data from permanent observing ocean ships. Earliest data is 1945 and latest data is 1991. Added in June 2006 are station and line P profile data extracted from WOD05.